2021
DOI: 10.3390/su13041818
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Sustainability of Extensive Livestock Farms on the Common Grasslands of the Natural Park Sierra de Grazalema

Abstract: The communal pastures of the Natural Park Sierra de Grazalema are grazed by a total of 23 extensive herds, of which 75% are certified as organic, although only 39% are subsidized for being organic. In a previous research work, these farms were characterized and classified into four typologies: group 1 (farms of intermediate size and without sheep), group 2 (large and very extensive farms), group 3 (farms with sheep suitable for both meat and milk) and group 4 (farms with dairy goat milk and without cattle). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Moreover, the optimization of labour management during intensive times of the year should improve sustainability. It could be possible to improve the economic performance of livestock farms by modifying the conditions and criteria for obtaining European Common Agricultural Policy (CAP) subsidies in favor of environmental conservation, which could enhance the sustainability of livestock farms [61].…”
Section: Contrast To Prior Literaturementioning
confidence: 99%
“…Moreover, the optimization of labour management during intensive times of the year should improve sustainability. It could be possible to improve the economic performance of livestock farms by modifying the conditions and criteria for obtaining European Common Agricultural Policy (CAP) subsidies in favor of environmental conservation, which could enhance the sustainability of livestock farms [61].…”
Section: Contrast To Prior Literaturementioning
confidence: 99%
“…This means allowing farmers to reduce the production costs of pen building and feed provision, increasing earnings, and facilitating care. However, Delattre et al (2020) and Gaona et al (2021) reported that the weakness of an extensive livestock system is the requirement for an ample supply of input to maintain good livestock productivity. An extensive care system also tends to increase the risks of caring for and spreading diseases (Temple and Manteca 2020;Delsart et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Low quality forage results in lowered conversion of feed to meat (Terry et al, 2020). Additionally, insufficient pasture can reduce livestock productivity (Díaz-Gaona et al, 2021). Source: Processed primary data, 2020…”
Section: Financial Analyses Of Business Feasibilitymentioning
confidence: 99%